Update on anterior ankle impingement - Tanawat Vaseenon (2018)
Anterior ankle impingement results from an impingement of the ankle joint by a soft tissue or osteophyte formation at the anterior aspect of the distal tibia and talar neck. It often occurs secondary to direct trauma (impaction force) or repetitive ankle dorsiflexion (repetitive impaction and traction force). Chronic ankle pain, swelling, and limitation of ankle dorsiflexion are common complaints. Imaging is valuable for diagnosis of the bony impingement but not for the soft tissue impingement, which is based on clinical findings. MR imaging and MR arthrography are helpful in doubtful diagnoses and the identification of associated injuries. Recommended methods for initial management include rest, physical therapy, and shoe modification. If nonoperative treatment fails, arthroscopic bony or soft tissue debridement both offer significant symptomatic relief with long-term positive outcomes in cases that have no significant arthritic change, associated ligament laxity, and chondral lesion. © Springer Science+Business Media, LLC 2012.